Device and method for testing electronic conductivity of coated pole piece

By applying DC power at both ends of the Z-axis direction of the coated electrode sheet and measuring the voltage drop, the limitations of the coating electrode sheet conductivity test in the prior art are solved, and the accurate evaluation of the overall resistance of the electrode sheet and the applicability of a variety of coating materials are achieved.

CN119827580APending Publication Date: 2025-04-15HEYUAN LICHUANG (SUZHOU) NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510066549.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-16
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The prior art has limitations when testing the electronic conductivity of the coated electrode sheet. The four-probe method can only measure the surface resistance of the coating itself, and cannot fully reflect the overall resistance of the electrode sheet, and ignore the influence of the contact resistance, resulting in deviations in the test results.

Method used

A new two-point test method is adopted. By applying DC power at both ends of the Z-axis direction of the electrode sheet and measuring the voltage drop, combining with the pressurization device to ensure uniform mechanical stress. The calculated conductivity values ​​include coating resistance, contact resistance, etc., reflecting the real electronic path resistance in the electrode.

Benefits of technology

This method can accurately reflect the true resistance characteristics of coated electrode sheets, the test results are accurate and suitable for a variety of coating materials, with good compatibility and applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119827580A_ABST
    Figure CN119827580A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductivity testing, and particularly relates to a device and a method for testing the electronic conductivity of a coated pole piece. The testing device comprises an insulating sleeve, and an upper rod body and a lower rod body which can penetrate into the insulating sleeve; the insulating sleeve is provided with a vertically through accommodating hole; the bottom of the upper rod body is provided with a flat contact surface, and the bottom end of the upper rod body extends into the accommodating hole; the top of the lower rod body is provided with a flat contact surface, and the top end of the lower rod body extends into the accommodating hole; a coating pole piece is accommodated in a gap between the contact surface of the upper pole body and the contact surface of the lower pole body; the upper rod body and the lower rod body are both conductive, and an electrochemical workstation is connected between the upper rod body and the lower rod body; and a pressurizing device is used for applying extrusion force to the upper rod body and the lower rod body. Based on the testing device, the invention provides a convenient, accurate and reliable testing method which can accurately and comprehensively reflect the electrical characteristics of the coating pole piece in the actual working state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductivity testing, and in particular relates to a testing device and a testing method for the electronic conductivity of a coated electrode. Background Art

[0002] With the widespread use of lithium batteries and other secondary batteries, battery safety and performance optimization have become the focus of research. In order to prevent the occurrence of internal short circuits in batteries, many manufacturers choose to coat a layer of insulating material on the surface of the pole piece to form an electronic insulation layer.

[0003] How to evaluate the insulation effect of the coating, there is currently no convenient, accurate and reliable testing device and method. The commonly used method in the industry is to measure the electronic conductivity of the electrode in the XY direction through a four-probe surface resistance meter to evaluate the conductivity of the electrode. Although this method can provide certain data references, it has limitations when dealing with coated electrodes. Since the four-probe method is mainly aimed at the resistance characteristics within the plane, it can only measure the surface resistance of the coating itself, and cannot fully reflect the overall resistance of the electrode. Therefore, when using a four-probe surface resistance meter to test the coated substrate, the measured data is obviously one-sided and inaccurate.

[0004] In addition, traditional testing methods ignore the influence of various contact resistances that may exist under actual battery operating conditions, such as the contact resistance between the coating and the collector, the contact resistance between the sample and the test probe, etc., which further aggravates the deviation of the test results. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a device and method for testing the electronic conductivity of a coated electrode.

[0006] The present invention establishes a new fast and easy-to-use two-point method to determine the electronic conductivity of the coated electrode. Given a constant pressure on the test equipment to ensure uniform and constant mechanical stress during the analysis, by applying direct current at both ends of the electrode in the Z-axis direction and measuring the voltage drop, the electron transport characteristics over the entire electrode cross section can be determined while taking into account all battery-related resistances. The result obtained is an easily comparable relative resistivity value, including the coating resistance, the contact resistance between the coating and the adhered collector, and the contact resistance between the sample and the probe. This method not only makes the test equipment simple to set up, but also can reflect the resistance of the actual electron path in the electrode, and the test results are accurate.

[0007] The first aspect of the present invention is to provide a testing device for the electronic conductivity of a coated electrode, comprising an insulating sleeve and an upper rod body and a lower rod body that can be inserted into the insulating sleeve; the insulating sleeve has a receiving hole that passes through from top to bottom; the bottom of the upper rod body has a flat contact surface, and the bottom end of the upper rod body extends into the receiving hole; the top of the lower rod body has a flat contact surface, and the top end of the lower rod body extends into the receiving hole; the coated electrode is accommodated in the gap between the contact surface of the upper rod body and the contact surface of the lower rod body; both the upper rod body and the lower rod body are conductive, and an electrochemical workstation is connected between the upper rod body and the lower rod body; a pressurizing device applies a force to the upper rod body and the lower rod body, so that a preset extrusion pressure is maintained between the contact surface of the upper rod body and the upper surface of the coated electrode, and a preset extrusion pressure is maintained between the contact surface of the lower rod body and the lower surface of the coated electrode.

[0008] As a further optimization solution for the coated electrode electronic conductivity testing device, the pressurizing device is a tablet press, which applies extrusion force to the top of the upper rod body and the bottom of the lower rod body.

[0009] As a further optimization scheme of the coated electrode electronic conductivity testing device, an upper retaining seat is fixed on the top of the upper rod body, and the top of the upper retaining seat has a flat force-bearing surface with an area larger than the cross-section of the upper rod body; a lower retaining seat is fixed on the top of the upper rod body, and the bottom of the lower retaining seat has a flat force-bearing surface with an area larger than the cross-section of the lower rod body.

[0010] As a further optimization scheme of the coated electrode electronic conductivity testing device, the inner wall of the insulating sleeve has an internal thread, the outer walls of the upper rod body and the lower rod body have external threads, the bottom of the upper rod body is connected to the insulating sleeve thread, and the top of the lower rod body is connected to the insulating sleeve thread; the pressurizing device applies extrusion force by adjusting the rotation angle of the upper rod body relative to the insulating sleeve and / or the rotation angle of the lower rod body relative to the insulating sleeve.

[0011] As a further optimization solution for the coated electrode electronic conductivity testing device, the inner wall of the insulating sleeve has two upper and lower sections of internal threads with opposite spiral directions. When pressurized, the relative angle between the upper rod body and the lower rod body is maintained, and the angle between the upper rod body and the insulating sleeve and the angle between the lower rod body and the insulating sleeve are changed synchronously.

[0012] As a further optimization scheme of the coated electrode electronic conductivity test device, the terminal is made of annealed materials, and the materials are selected from: 316L stainless steel, carbon steel, bearing steel, chromium 12 steel; the upper rod body and the lower rod body are made of annealed materials, and the materials are selected from: 316L stainless steel, carbon steel, bearing steel, chromium 12 steel.

[0013] As a further optimization solution for the coated electrode electronic conductivity testing device, the insulating sleeve is made of polytetrafluoroethylene or polyetheretherketone.

[0014] The second aspect of the present invention is to provide a method for testing the electronic conductivity of a coated electrode, using the above-mentioned testing device, comprising the following steps:

[0015] Step S1: cutting the coated electrode to be tested into test pieces slightly smaller than the size of the accommodating hole of the insulating sleeve;

[0016] Step S2: measuring the thickness of the test piece, recorded as L;

[0017] Step S3: measuring the cross-sectional area of ​​the test piece, recorded as A;

[0018] Step S4: placing the test piece between the upper rod and the lower rod of the test device, and preventing the edge of the test piece from contacting the inner wall of the insulating sleeve;

[0019] Step S5: using a pressure device to apply a force to the upper rod and the lower rod so that both sides of the test piece are subjected to a constant squeezing force;

[0020] Step S6: Turn on the electrochemical workstation and measure the electronic impedance R of the test piece through the DC polarization curve;

[0021] Step S7: Calculate the conductivity according to the following formula:

[0022] σ=1 / ρ=(1 / R)×(L / A);

[0023] in,

[0024] σ: electrical conductivity;

[0025] ρ: resistivity;

[0026] R: resistance;

[0027] L: sample length;

[0028] A: sample cross-sectional area.

[0029] As a further optimization scheme of the above test method, the voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0030] As a further optimization scheme of the above test method, the squeezing force of the upper rod body and the lower rod body on the test piece is preferably 200 kg.

[0031] As a further optimization scheme of the above-mentioned test method, the coating material of the coated pole piece can preferably be a metal oxide material such as aluminum oxide, zirconium oxide, magnesium oxide, or can also be a solid electrolyte material such as lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium phosphorus sulfur chlorine, and lithium zirconium chloride.

[0032] Beneficial Effects

[0033] The device and method for testing the electronic conductivity of the coated electrode provided by the present invention evaluates the electronic transmission characteristics of the entire electrode cross section by applying current in the Z-axis direction of the electrode and measuring the voltage drop, including all battery-related resistances, such as coating resistance, contact resistance, etc. This can more accurately reflect the true resistance characteristics of the coated electrode than the traditional four-probe method.

[0034] The testing device provided by the present invention has a simple structure and is easy to operate. It can complete the testing of samples without complicated equipment or steps, thereby shortening the experimental preparation time and improving work efficiency.

[0035] The testing method of the present invention can be adapted to a variety of coating materials, whether metal oxides or solid electrolyte materials, and can be tested by this method, and has good compatibility and wide applicability to different types of coating materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 Schematic diagram of the structure of the test device for the electronic conductivity of the coated electrode.

[0037] In the figure: 1. Insulating sleeve; 2. Upper rod body; 3. Lower rod body; 4. Upper retaining seat; 5. Lower retaining seat; 6. Electrochemical workstation. DETAILED DESCRIPTION

[0038] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.

[0039] The test device used in the following embodiments is as follows Figure 1 As shown, it includes an insulating sleeve 1 and an upper rod body 2 and a lower rod body 3 that can be inserted into the insulating sleeve 1; the insulating sleeve 1 has a receiving hole that passes through from top to bottom; the bottom of the upper rod body 2 has a flat contact surface, and the bottom end of the upper rod body 2 extends into the receiving hole; the top of the lower rod body 3 has a flat contact surface, and the top end of the lower rod body 3 extends into the receiving hole; the coated electrode is accommodated in the gap between the contact surface of the upper rod body 2 and the contact surface of the lower rod body 3; both the upper rod body 2 and the lower rod body 3 are conductive, and an electrochemical workstation 6 is connected between the upper rod body 2 and the lower rod body 3; a pressurizing device applies a force to the upper rod body 2 and the lower rod body 3, so that a preset extrusion pressure is maintained between the contact surface of the upper rod body 2 and the upper surface of the coated electrode, and a preset extrusion pressure is maintained between the contact surface of the lower rod body 3 and the lower surface of the coated electrode. An upper retaining seat 4 is fixed to the top of the upper rod 2, and the top of the upper retaining seat 4 has a flat force-bearing surface with an area larger than the cross section of the upper rod 2; a lower retaining seat 5 is fixed to the top of the upper rod 2, and the bottom of the lower retaining seat 5 has a flat force-bearing surface with an area larger than the cross section of the lower rod 3. The pressure device used in the embodiment is a tablet press, which applies a squeezing force to the top of the upper rod 2 and the bottom of the lower rod 3.

[0040] Example 1

[0041] Cut the 2um alumina coated positive electrode sheet into small discs with a diameter of 10mm. The thickness of the electrode sheet tested by the micrometer is 144um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Put the insulating sleeve 1 on the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0042] Example 2

[0043] Cut the 4um alumina coated positive electrode sheet into small discs with a diameter of 10mm. The thickness of the electrode sheet tested by the spiral micrometer is 144um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Put the insulating sleeve 1 on the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0044] Example 3

[0045] Cut the surface-coated 4um solid electrolyte coating positive electrode sheet into small discs with a diameter of 10mm. The thickness of the electrode sheet tested by the spiral micrometer is 144um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Sleeve the insulating sleeve 1 over the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0046] Example 4

[0047] Cut the negative electrode sheet coated with 4um alumina coating into small discs with a diameter of 10mm. The thickness of the electrode sheet tested by the spiral micrometer is 144um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Put the insulating sleeve 1 on the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0048] Example 5

[0049] Cut the negative electrode sheet coated with 4um solid electrolyte coating into small discs with a diameter of 10mm. The thickness of the electrode sheet tested by the spiral micrometer is 144um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Put the insulating sleeve 1 on the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0050] Example 6

[0051] Cut the uncoated positive electrode sheet into small discs with a diameter of 10 mm. The thickness of the electrode sheet tested by the micrometer screw is 144 um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Put the insulating sleeve 1 on the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0052] Example 7

[0053] Cut the uncoated negative electrode sheet into small discs with a diameter of 10 mm. The thickness of the electrode sheet tested by the micrometer screw is 144 um. Place the small disc on the top of the lower rod 3, and keep the small disc from exceeding the top edge of the lower rod 3. Put the insulating sleeve 1 on the lower rod 3. During the insertion process, keep the small disc in the center of the lower rod 3, and the small disc does not contact the insulating sleeve 1. Then insert the upper rod 2 into the other end of the insulating sleeve 1. Connect a wire to the terminal of the upper rod 2 and the electrochemical workstation 6, and connect the other wire to the terminal of the lower rod 3 and the electrochemical workstation 6. Use a tablet press to apply a 200 kg extrusion force to the upper rod 2 and the lower rod 3. The electronic impedance R is tested by the DC polarization curve of the electrochemical workstation 6, and the conductivity of the coated electrode is calculated according to the conductivity calculation formula σ=1 / ρ=(1 / R)×(L / A) in combination with the thickness L and the area A of the coated electrode. The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

[0054] The test results are shown in Table 1. It is found that the electronic conductivity of the negative electrode coated electrode is slightly different from that of the uncoated negative electrode. This is because the negative electrode material itself has good conductivity and the coating-negative electrode interface electron transmission resistance is small. Although the coating is an insulating material, after the coated electrode is compacted, the negative electrode material plays a good role in electron transmission between the coatings. It can also be seen from Table 1 that the electronic conductivity of the positive electrode coated electrode is significantly different from that of the uncoated positive electrode. This is because the positive electrode material has poor conductivity and the coating material is an insulating material, which leads to a large electron transmission resistance in the coating and the coating-positive electrode interface. In addition, it can be seen that the thickness of the coating has a great influence on the coated electrode, which is mainly because the electron migration distance in the coating is long and the electron transmission resistance is large.

[0055] Table 1 Test values ​​of electronic conductivity of electrodes with different coatings

[0056]

[0057] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. A device for testing the electronic conductivity of a coated electrode, characterized in that: The invention comprises an insulating sleeve (1) and an upper rod body (2) and a lower rod body (3) which can be inserted into the insulating sleeve (1); the insulating sleeve (1) has a receiving hole which passes through from top to bottom; the bottom of the upper rod body (2) has a flat contact surface, and the bottom end of the upper rod body (2) extends into the receiving hole; the top of the lower rod body (3) has a flat contact surface, and the top end of the lower rod body (3) extends into the receiving hole; a gap between the contact surface of the upper rod body (2) and the contact surface of the lower rod body (3) is provided. The coated electrode is received; the upper rod body (2) and the lower rod body (3) are both conductive, and an electrochemical workstation (6) is connected between the upper rod body (2) and the lower rod body (3); a pressurizing device applies a force to the upper rod body (2) and the lower rod body (3), so that a preset extrusion pressure is maintained between the contact surface of the upper rod body (2) and the upper surface of the coated electrode, and a preset extrusion pressure is maintained between the contact surface of the lower rod body (3) and the lower surface of the coated electrode.

2. The device for testing the electronic conductivity of a coated electrode according to claim 1, characterized in that: The pressure device is a tablet press, which applies a squeezing force to the top of the upper rod body (2) and the bottom of the lower rod body (3).

3. The device for testing the electronic conductivity of a coated electrode according to claim 1, characterized in that: An upper retaining seat (4) is fixed on the top of the upper rod body (2), and the top of the upper retaining seat (4) has a flat force-bearing surface with an area larger than the cross-section of the upper rod body (2); a lower retaining seat (5) is fixed on the top of the upper rod body (2), and the bottom of the lower retaining seat (5) has a flat force-bearing surface with an area larger than the cross-section of the lower rod body (3).

4. The device for testing the electronic conductivity of a coated electrode according to claim 1, characterized in that: The inner wall of the insulating sleeve (1) has an internal thread, and the outer walls of the upper rod body (2) and the lower rod body (3) have external threads; the bottom of the upper rod body (2) is threadedly connected to the insulating sleeve (1), and the top of the lower rod body (3) is threadedly connected to the insulating sleeve (1); the pressurizing device applies a squeezing force by adjusting the rotation angle of the upper rod body (2) relative to the insulating sleeve (1) and / or the rotation angle of the lower rod body (3) relative to the insulating sleeve (1).

5. The device for testing the electronic conductivity of a coated electrode according to claim 4, characterized in that: The inner wall of the insulating sleeve (1) has two upper and lower sections of internal threads with opposite spiral directions. When pressure is applied, the relative angle between the upper rod body (2) and the lower rod body (3) is maintained, and the angle between the upper rod body (2) and the insulating sleeve (1) and the angle between the lower rod body (3) and the insulating sleeve (1) are changed synchronously.

6. The device for testing the electronic conductivity of a coated electrode according to claim 1, characterized in that: The terminal is made of annealed material, which is selected from the group consisting of 316L stainless steel, carbon steel, bearing steel, and chrome 12 steel; the upper rod body (2) and the lower rod body (3) are made of annealed material, which is selected from the group consisting of 316L stainless steel, carbon steel, bearing steel, and chrome 12 steel.

7. The device for testing the electronic conductivity of a coated electrode according to claim 1, characterized in that: The insulating sleeve (1) is made of polytetrafluoroethylene or polyetheretherketone.

8. A method for testing the electronic conductivity of a coated electrode, characterized in that: The test device according to any one of claims 1 to 7 comprises the following steps: Step S1: cutting the coated electrode to be tested into test pieces slightly smaller than the size of the receiving hole of the insulating sleeve (1); Step S2: measuring the thickness of the test piece, recorded as L; Step S3: measuring the cross-sectional area of ​​the test piece, recorded as A; Step S4: placing the test piece between the upper rod (2) and the lower rod (3) of the test device, and preventing the edge of the test piece from contacting the inner wall of the insulating sleeve (1); Step S5: using a pressure device to apply a force to the upper rod body (2) and the lower rod body (3) so that both sides of the test piece are subjected to a constant squeezing force; Step S6: starting the electrochemical workstation (6) and measuring the electronic impedance R of the test piece through a DC polarization curve; Step S7: Calculate the conductivity according to the following formula: σ=1 / ρ=(1 / R)×(L / A); in, σ: electrical conductivity; ρ: resistivity; R: resistance; L: sample length; A: sample cross-sectional area.

9. The method for testing the electronic conductivity of a coated electrode according to claim 8, characterized in that: The voltage range of the DC polarization curve test process is 0-10V, and the response current range is 0-2A.

10. The method for testing the electronic conductivity of a coated electrode according to claim 8, characterized in that: The coating material of the coated pole piece is selected from the group consisting of: aluminum oxide, zirconium oxide, magnesium oxide, lithium aluminum titanium phosphate, lithium lanthanum zirconium oxide, lithium lanthanum zirconium tantalum oxide, lithium phosphorus sulfur chlorine, and lithium zirconium chloride.